Overexpression and site-directed mutagenesis of the succinyl-CoA synthetase of Escherichia coli and nucleotide sequence of a gene (g30) that is adjacent to the suc operon. - Buck, D (1989)
The succinyl-CoA synthetase of Escherichia coli is encoded by two genes, sucC (beta subunit) and sucD (alpha subunit), which are distal genes in the sucABCD operon. They are expressed from the suc promoter, which also expresses the dehydrogenase and dihydrolipoyl succinyl-transferase subunits of the 2-oxoglutarate dehydrogenase complex. Strategies have now been devised for the site-directed mutagenesis and independent expression of the succinyl-CoA synthetase (alpha 2 beta 2 tetramer) and the individual subunits. These involve (1) subcloning a promoterless sucCD fragment downstream of the lac promoter in M13mp10, and (2) precise splicing of the suc coding regions with the efficient atpE ribosome-binding site and expression from the thermoinducible lambda promoters in the pJLA503 vector. Succinyl-CoA synthetase specific activities were amplified 40-60-fold within 5 h of thermoinduction of the lambda promoters, and the alpha and beta subunits accounted for almost 30% of the protein in supernatant fractions of the cell-free extracts. Site-directed mutagenesis of potential CoA binding-site residues indicated that Trp-43 beta and His-50 beta are essential residues in the beta-subunit, whereas Cys-47 beta could be replaced by serine without inactivating the enzyme. No activity was detected after the histidine residue at the phosphorylation site of the alpha-subunit was replaced by aspartate (His-246 alpha----Asp), but this alteration seemed to have a deleterious effect on the accumulation of the enzyme in cell-free supernatant extracts. The nucleotide sequence of an unidentified gene (g30) that is adjacent to the sucABCD operon was defined by extending the sequence of the citric acid cycle gene cluster by 818 bp to 13379 bp: gltA-sdhCDAB-sucABCD-g30. This gene converges on the suc operon and encodes a product (P30) that contains 230 amino acids (Mr 27,251). Highly significant similarities were detected between the N-terminal region of P30 and those of GENA [the product of another unidentified gene (geneA) located upstream of the aceEF-lpd operon], and GNTR (a putative transcriptional repressor of the gluconate operon of Bacillus subtilis). Possible roles for GENA and P30 as transcriptional regulators of the adjacent operons encoding the pyruvate and 2-oxoglutarate dehydrogenase complexes are discussed.